La Traducción del Almanacco Universale del Pescatore di Chiaravalle: origen y evolución del Sarrabal en España en el siglo XVII (Carte Romanze, 2022)
In the last third of the 17th century, an editorial product with wide European circulation was very successful in the book market and would become one of the most relevant and widely read almanacs in the Iberian Peninsula: the Sarrabal de Milán. This study aims to delve into the origin of this almanac in Spanish, published in Barcelona and Madrid, as a translation of the Milanese Almanacco Universale del Pescatore di Chiaravalle. These two studies, both editorial and linguistic, aim at focusing on the appropriations carried out by the Spanish Sarrabal and discern the degree of adaptation and translation with respect to its Italian counterpart.